Pengakuan terhadap Masyarakat Hukum Adat Marga Sarampas dan Penguasaan Hak Atas Tanahnya - Hendra Herman (Wajah Hukum, 2021)
The decision of the Constitutional court (MK) Numbere 35/PUU-X/2012 has implications for state recognition of the traditional rights of indigenous peoples in the form of custimary forests which have have been neglected. The study aims to determine the legal position of the indigenous people of Marga Sarampas in controlling their land rights. The formulation of the problems raised in this research are (1) how is the recognition and protection of the indigenous peoples of Marga Sarampas; (2) how the rights to land of the indigenous people of Marga Sarampas.